Impact of heat stress on expression kinetics of HSP27 in cardiac cells of goats. Issue 6 (17th August 2020) - Parida, S.; Mishra, S. R.; Mishra, C.; Dalai, N.; Mohapatra, S.; Mahapatra, A. P. K.; Kundu, A. K.
ABSTRACT: The present study was aimed to investigate the effect of heat stress on the expression kinetics of heat shock protein 27 (HSP27) mRNA in cultured cardiac cells of goats. The heart tissues ( n = 6) from different goats were used for the culture study. The cardiac cells obtained from different heart tissues were cultured in 24-well culture plates and incubated in a humidified CO2 (5%) incubator at 37°C. The cardiac cells were allowed to become 75–80% confluent after 72 h of incubation. Thereafter, the cardiac cells were subjected to heat exposure at 42°C (heat exposed) for 0, 20, 60 and 100 min. The cardiac cells exposed to heat stress at 42°C for 0 min was taken as control. The relative abundance of HSP27 mRNA did not change at 20 min of heat exposure and increased ( P < 0.05) at 60 and 100 min of heat exposure as compared to control. However, the highest ( P < 0.05) relative abundance of HSP27 mRNA was noticed at 100 min of heat exposure. The present findings indicate that HSP27 could possibly promote thermo-protection to cardiac cell from the detrimental effect of heat stress.